A Dual Mechanism of the Drag Reduction by Rigid Polymers and Cationic Surfactant: Complex and Nanofluids of Xanthan Gum and Hexadecyl Trimethyl Ammonium Chloride - Abdulbari, Hayder A.; Oluwasoga, Akindoyo Edward; Zainab, Yousif (eSAT Publishing House Pvt. Ltd., 2015)
Several approaches have been employed to reduce the high cost of energy associated with the way liquids are transported in pipelines. Polymers have been widely explored to replace the pumping stations and other high energy cost mechanisms, but degrade over a period of time due to the accompanying turbulent mode of such transportation. Surfactants which are better alternatives with the ability to reenact their lost efficiency, are less effective, there is therefore the need for an alternative mechanism for drag reduction. In this present work, drag reduction efficacy of dispersed silica nanoparticle additives with polar additives as complexes and nanofluid have been investigated as a new method to reduce drag. Thus the present work was carried out with Xanthan gum which is able to withstand degradation compared to the flexible polymers, hexadecyltrimethyl ammonium chloride as the surfactant and sodium salicylate as the counterion. In the study both complexes and nanofluid were able to reduce drag as well as withstand shear stresses, although at different concentration which could be as a result of the different approaches of working, about 60% drag reduction was observed. It could thus be concluded that, these materials are able to reduce drag both as complex or nanofluid, only that, they could do that at different concentrations.